2020
DOI: 10.1111/ajsp.12441
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of living historical memories and news source with national identity: A latent class analysis

Abstract: Previous research has suggested that national identity is associated with one's memory of the nation's past (i.e., historical events) and current information received from mass media. This study tied these two areas of research to examine if narratives of historical memory, the valence of those memories, and preferred media use/news sources (traditional vs. digital) would be associated with national identity, trust in government, and system justification. Data were obtained through the Digital Influence II Sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 68 publications
1
8
0
Order By: Relevance
“…Consistent with the previous study about the Philippines, Li et al (2021) found in a study of Hong Kong Chinese living historical memory (LHM; see that the mass communication medium carried implications for the message people received. In both societies, Internet-based mass media carried a message that could be regarded as subversive to official national accounts.…”
Section: Heterogeneity Of Collective Remembering As Mediated By Mass Communications and Age Cohortssupporting
confidence: 89%
“…Consistent with the previous study about the Philippines, Li et al (2021) found in a study of Hong Kong Chinese living historical memory (LHM; see that the mass communication medium carried implications for the message people received. In both societies, Internet-based mass media carried a message that could be regarded as subversive to official national accounts.…”
Section: Heterogeneity Of Collective Remembering As Mediated By Mass Communications and Age Cohortssupporting
confidence: 89%
“…Deeper analyses of LHM for particular countries (e.g., Bou Zeineddine & Qumseya, in press; Li, Lin, & Maer, in press), and an overall content analysis (Choi et al, under review) suggest that there is no single “master narrative” knitting together the nominations in most societies. In some communication contexts, like Hong Kong (where there is the salient context of protest against Beijing), certain configurations of historical events were linked to anti-governmental points of view (Li, Lin, & Maer, in press). In others, like Morocco (where there is a stable monarchy) they were connected to greater system support (Bou Zeineddine & Qumseya, in press).…”
Section: Discussionmentioning
confidence: 99%
“…But there should be limits to the state’s ability to curate sympathetic collective remembering of events entering into living historical memory. These are constructed via multiple channels, only some of which are controlled by the state: see Li, Lin, and Maer’s (in press) study of social media and dissident LHM in Hong Kong. Scholars investigating officially sanctioned, top-down memories manufactured by the state tend to focus on the production of a “suitable past” without providing evidence of how these productions are received by their intended audiences.…”
Section: Official Historical Narratives As a Product Of The State Liv...mentioning
confidence: 99%
“…The data on living historical memories obtained through the Digital Influence II Survey has been analyzed in several studies by using latent class analysis. Common to these studies (Bou Zeineddine & Qumseya, 2020; Li et al., 2020; Vincze et al., in press) is the finding of a two-class structure characterizing living historical memory. In the present study, a different type of analysis was employed.…”
Section: Discussionmentioning
confidence: 99%